A note on the existence of soliton solutions in the chernsimonscp(1) model - Sourrouille, Lucas (2011)
We study a gauged ChernSimonsCP(1) system. We show that contrary to previous claims, the model in the absence of a potential term cannot support finite size soliton solution in R 2. © 2011 World Scientific Publishing Company.